Approvisionnement En Eau Dans La Ville De Brazzaville, Congo - Célestine, Nkounkou Loumpangou; Félicien, Louzayadio Mvouezolo Raison; Nicolas, Ayessou; Murphy, Elouma Ndinga Arnold; Christian, Ngakegni-Limbili Adolphe; Gueye, Mar Diop Codou; Jean - Maurille, Ouamba (European Scientific Journal, ESJ, 2017)
The difficulty of water supply is a major problem faced by the households of Brazzaville in Congo. The objective of this study is to list and identify the different types of water used, and to assess the general hygiene of households. The method used in this prospective study is based on an onsite survey and direct measurement. The survey involves administering a questionnaire to the households in the 9 districts of the city of Brazzaville. 630 households were surveyed. 70 households were drawn in this study and were selected in each borough. There are many sources of water. Overall, 80.16% of households consume water from the SNDE. The survey revealed that 71.00% of households walk on foot to get access to water supply. Plastic cans and buckets are used more in the transportation (43.00 and 37.00 %) and storage (45.00 and 39.00 %) of water. The water storage period is relatively long. It can hold water from 3 days (21.00%) to more than one week (13.00 %) for some households. Analysis of the results of the survey showed that the sources of water supply are diversified. This diversification is due to the phenomenon of shortage and/or repeated water cut recorded by households. Water supply, transport and storage practices, and the cleaning of water containers highlight the precarious conditions of hygiene and sanitation households in the city of Brazzaville